KEBUTUHAN PELAYANAN KESEHATAN PENYANDANG DISABILITAS: LITERATURE REVIEW - Roland Lekatompessy (Indonesian Journal of Nursing Scientific, 2024)
The health care needs of people with disabilities. Every person, including individuals with disabilities, has an equal right to optimal healthcare services. Efforts to prevent disabilities and ensure that people with disabilities remain healthy, productive, and dignified include fulfilling their rights to access healthcare facilities. The study aims to learn about the health-care needs of people with disabilities. This article employs a literature review method, utilizing articles and journals sourced from searches conducted on PubMed and Google Scholar. Based on the analysis of 10 articles, several healthcare needs for people with disabilities were identified, including accessibility of healthcare services, acceptance by healthcare professionals, social support, rehabilitation, and the use of assistive technology to facilitate daily needs. The healthcare needs of individuals with disabilities involve access, acceptance, education for healthcare professionals, as well as the provision of special facilities and support.